Thermal and Electrical Performance of Uncooled, Nature-Cooled, and Photovoltaic Thermal Module - Pushpendu Dwivedi; Sujay Ashwinraj Ganesh; Kumarasamy Sudhakar; Archana Soni; S. Shanmuga Priya (International Journal of Photoenergy)
The experimental study is aimed at analyzing photovoltaic module’s thermal and electrical performance (PV) with back surface cooling under Malaysian tropical climate conditions. The performance of a passively cooled PV module integrated with biomaterial (moist coconut fiber) was compared with a photovoltaic thermal (PVT) system with water circulation at the rate of 0.02 kg s-1 and a reference PV module. The study observed that the passively cooled PV module succeeded in reducing the module surface temperature by more than 20%. However, the PVT system reduced the temperature only by less than 17%. The electrical energy efficiency was improved remarkably in the passively cooled PV module by almost 11%, but the PVT system managed to increase the electrical efficiency by 9%, approximately. It can be concluded that nature-inspired coconut fiber-based cooling can be one of the potential alternatives to active cooling methods.